Individuals with intellectual disabilities and second language acquisition: a framework for approaching inclusive foreign language instruction - Mally, Natacha Hélène Gilberte (Kansas State University, 2019)
Special education under the Individuals with Disabilities Education Act (IDEA) is aimed at providing each eligible child with an appropriate education tailored to their needs in order to be successful in life. Agreeing on what those needs are can be difficult for educators and parents. For some children the goal can be going to college or finding employment; for others, it is independent living. Even though inclusion and learning in the least restrictive environment is currently the norm in the American public-school system, where second language education is concerned, children with an Intellectual Disability (ID) do not receive the same opportunities as their typically developing peers. Instead of integrating children with an ID in existing world language classes, providing differentiated instruction, or offering different ways to obtain world language credit, language waivers are often automatically provided in order to ensure graduation. If parents express a wish to maintain a home language other than the main instructional language, they are generally discouraged by both the medical community and educational professionals, and the heritage language is not integrated in instruction. However, those recommendations are not always grounded in scientific research, but rather on assumptions, a lack of resources, or a failure to understand the need for world language education. This report synthesizes relevant research on the effects of learning a second language and explores the potential benefits for individuals with an ID. In addition, current teaching techniques are reviewed, and suggestions are provided for how teachers may want to adapt these techniques for language instruction with children with an ID.
Keywords: Intellectual Disability; Second language acquisition; Gamification; Home language; Differentiation; Inclusive L2 classrooms